1992
DOI: 10.1148/radiology.182.2.1732979
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent rectal cancer and scar: differentiation with PET and MR imaging.

Abstract: The value of positron emission tomography (PET) and magnetic resonance (MR) imaging in differentiating recurrent rectal cancer and scar was investigated. PET with fluorine-18 2-fluoro-2-deoxy-D-glucose (FDG) and MR imaging were performed in 15 patients with suspected recurrence. FDG accumulation in the mass was measured by means of the differential absorption ratio (DAR). All 11 patients with confirmed recurrent rectal cancer had increased accumulation of FDG in the mass (DAR = 4.73 +/- 2.28). Low FDG accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
4

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(46 citation statements)
references
References 0 publications
2
40
0
4
Order By: Relevance
“…Patients with presacral masses and suspected local recurrences were first studied by the group from the German Cancer Research Centre in Heidelberg. In several successive studies, these investigators [91,144] demonstrated the value of PET in differentiating scar tissue and tumour in this setting, a finding later confirmed by Ito et al and Schiepers et al [145,146] (Table 3). In contrast, when a presacral mass is identified on CT, it is very difficult to diagnose its origin: scar, fibrotic tissue or tumoral recurrence.…”
Section: Colorectal Carcinomamentioning
confidence: 79%
“…Patients with presacral masses and suspected local recurrences were first studied by the group from the German Cancer Research Centre in Heidelberg. In several successive studies, these investigators [91,144] demonstrated the value of PET in differentiating scar tissue and tumour in this setting, a finding later confirmed by Ito et al and Schiepers et al [145,146] (Table 3). In contrast, when a presacral mass is identified on CT, it is very difficult to diagnose its origin: scar, fibrotic tissue or tumoral recurrence.…”
Section: Colorectal Carcinomamentioning
confidence: 79%
“…MR imaging in the differential diagnosis between recurrent tumour and postoperative scar (Ito et al, 1992;Takeuchi et al, 1999). The values of CEA scintigraphy and dynamic MR imaging have also been evaluated (Muller-Schimpfle et al, 1993;Blomqvist et al, 1996;Jarv et al, 2000;Torricelli et al, 2003).…”
Section: Igg-ferumoxidesmentioning
confidence: 99%
“…In their rat model, the bladder was irrigated before measurement of the uptake of '*FDG in the tumour, and they reported a higher "FDG concentration in urine than in tumour tissue. There are also reports that suggest that 18FDG is useful in diagnosis of recurrences of colorectal tumours (4). In these reports, the patient was instructed to urinate before transmission and emission scanning when a single image was performed.…”
Section: Discussionmentioning
confidence: 99%